The factor of public service organizations (the study of service quality) - Amir Mahmud, Firdaus, Dwi Oktisari, (Opción, 2019)
This study identified factors affecting public services organization which contribute to the highest and lowest on public services. This study used a quantitative design explanatory survey to explain the causal relationship between the variables through hypothesis testing. The results of the organizational factors affect the quality of public services, where the organizational factor of all valid indicator, the most dominant indicator in measuring organizational factors are indicators, procedures, policies and division of labor. In conclusion, the tasks specialization needs to be improved in order to upgrade organizational performance as well as the skills, duties and responsibilities each employee.